Outcomes of antiretroviral therapy in children in Asia and Africa: A comparative analysis of the IeDEA pediatric multiregional collaboration - Valeriane Leroy (2018)
BACKGROUND: We investigated 18-month incidence and determinants of death and loss to follow-up of children after antiretroviral therapy (ART) initiation in a multiregional collaboration in lower-income countries. METHODS: HIV-infected children (positive polymerase chain reaction < 18 months or positive serology ≥18 months) from International Epidemiologic Databases to Evaluate AIDS cohorts, < 16 years, initiating ART were eligible. A competing risk regression model was used to analyze the independent risk of 2 failure types: death and loss to follow-up ( > 6 months). FINDINGS: Data on 13,611 children, from Asia (N = 1454), East Africa (N = 3114), Southern Africa (N = 6212), and West Africa (N = 2881) contributed 20,417 person-years of follow-up. At 18 months, the adjusted risk of death was 4.3% in East Africa, 5.4% in Asia, 5.7% in Southern Africa, and 7.4% in West Africa (P = 0.01). Age < 24 months, World Health Organization stage 4, CD4 < 10%, attending a private sector clinic, larger cohort size, and living in West Africa were independently associated with poorer survival. The adjusted risk of loss to follow-up was 4.1% in Asia, 9.0% in Southern Africa, 14.0% in East Africa, and 21.8% in West Africa (P < 0.01). Age < 12 months, nonnucleoside reverse transcriptase inhibitor I-based ART regimen, World Health Organization stage 4 at ART start, ART initiation after 2005, attending a public sector or a nonurban clinic, having to pay for laboratory tests or antiretroviral drugs, larger cohort size, and living in East Africa or West Africa were significantly associated with higher loss to follow-up. CONCLUSIONS: Findings differed substantially across regions but raise overall concerns about delayed ART start, low access to free HIV services for children, and increased workload on program retention in lower-income countries. Universal free access to ART services and innovative approaches are urgently needed to improve pediatric outcomes at the program level. Copyright © 2012 by Lippincott Williams & Wilkins.